2004
DOI: 10.1080/00071660400014267
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor use, tonic immobility, heterophil/lymphocyte ratio and feather condition in free-range laying hens of different genotype

Abstract: 1. Movement (frequency of changes) between inside and outside housing areas, time spent in each area, tonic immobility (TI) and differential blood cell counts were studied in relation to feather condition in laying hens of two genotypes, white (LSL) and brown (LT). 2. From 18 weeks of age, LSL and LT were kept in 4 groups of 50 birds in a poultry house with passages to a roofed scratching room and a grassland area with a stocking density of one bird/10 m2. 3. All birds had transponders to record the movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 29 publications
8
56
2
Order By: Relevance
“…This finding implies a negative association between range use and fearfulness. Mahboub et al (2004) also found a negative correlation between time spent outside and TI duration. While it is generally assumed that birds with lower levels of fearfulness are more likely to venture outside, this causal relationship has yet to be confirmed.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This finding implies a negative association between range use and fearfulness. Mahboub et al (2004) also found a negative correlation between time spent outside and TI duration. While it is generally assumed that birds with lower levels of fearfulness are more likely to venture outside, this causal relationship has yet to be confirmed.…”
Section: Discussionmentioning
confidence: 72%
“…The majority of studies, however, report an inverse association between range use and plumage damage (Bestman and Wagenaar, 2003). Mahboub et al (2004) noted a negative correlation between feather damage and time spent on a grassland area outside, and Nicol et al (2003) found that in a multivariate model based on farmers' reports, feather-pecking occurred at higher levels when fewer birds used the outdoor range. Green et al (2000) conducted a cross-sectional survey of farmers and found similar results, where there was an association between lower range usage and feather-pecking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood was collected in EDTA tubes for blood smear preparation. The blood smears were stained [5,6] with Wright's stain in a concentration of 0.3% (Sigma Chemical Co., St. Louis, MO). Blood sample collection and the staining of the blood smear was performed to calculate the percentage of lymphocytes in a white blood cell (WBC) differential.…”
Section: A Research Designmentioning
confidence: 99%